PERAN PENGGUNAAN PUPUK PADA KINERJA PRODUKSI TANAMAN PANGAN INDONESIA - Pamuncak, Ririn; Arifin, Bustanul; Kasymir, Eka (Jurnal Ilmu-Ilmu Agribisnis, 2018)
This study aims to analyze the share of fertilizer costs on the total cost of crop and   the effect of fertilizer application on the performance of crop production in Indonesia.  The data used in the study was time series data, it was collected from FAOSTAT published Food and Agriculture Organization (FAO) and Statistics Center Bureou (BPS). The first objective was analyzed by descriptive statistics, whereras the second objective was analyzed by econometrics techniques, namely, linear production function, logarithmic function and quadratic function.  The results showed that the percentage fertilizer cost on the total cost of crop production were quite small compared to the cost of labor and land rental, which were 10.40 percent for wetland paddy, 7.80 percent for upland paddy, 12.00 percent for maize, and 4.80 percent for soybean.  The applications of fertilizer played important roles in production performance of paddy, maize, and soybean.  The magnitude and significant level of each fertilizer differ by crop production.  The study gives better policies to secure the availability of fertilizer to improve the performance of Indonesian crop production.Key words: cost,  fertilizer, production  function